(untitled) (Nepal Journal of Environmental Science, 2014)
Improved cooking stove (ICS) has provided the emerging opportunities, especially in the developing nations, considering the fact that it is more efficient and environment friendly than conventional cooking stoves. The paper briefly discusses about the design optimization of ICS. Current models are designed predominantly based on maximum energy conversion rather than coupling it with the original habits of users. There are various factors to be considered during the design of the cooking stove. The optimum design has the maximum efficiency resulting in low carbon emission, low kitchen indoor pollution, low fuel wood consumption and finally conserves the environment.